Financial impact of reducing door-to-balloon time in ST-elevation myocardial infarction: a single hospital experience - Taillon Heather; Khot Monica B; Ramsey Curtis; Geddes Jason B; Johnson-Wood Michele L; Khot Umesh N; Todd Randall; Shaikh Saeed R; Berg William J (BMC Cardiovascular Disorders, 2009)
Abstract Background The impact of reducing door-to-balloon time on hospital revenues, costs, and net income is unknown. Methods We prospectively determined the impact on hospital finances of (1) emergency department physician activation of the catheterization lab and (2) immediate transfer of the patient to an immediately available catheterization lab by an in-house transfer team consisting of an emergency department nurse, a critical care unit nurse, and a chest pain unit nurse. We collected financial data for 52 consecutive ST-elevation myocardial infarction patients undergoing emergency percutaneous intervention from October 1, 2004–August 31, 2005 and compared this group to 80 consecutive ST-elevation myocardial infarction patients from September 1, 2005–June 26, 2006 after protocol implementation. Results Per hospital admission, insurance payments (hospital revenue) decreased ($35,043 ± $36,670 vs. $25,329 ± $16,185, P = 0.039) along with total hospital costs ($28,082 ± $31,453 vs. $18,195 ± $9,242, P = 0.009). Hospital net income per admission was unchanged ($6962 vs. $7134, P = 0.95) as the drop in hospital revenue equaled the drop in costs. For every $1000 reduction in total hospital costs, insurance payments (hospital revenue) dropped $1077 for private payers and $1199 for Medicare/Medicaid. A decrease in hospital charges ($70,430 ± $74,033 vs. $53,514 ± $23,378, P = 0.059), diagnosis related group relative weight (3.7479 ± 2.6731 vs. 2.9729 ± 0.8545, P = 0.017) and outlier payments with hospital revenue>$100,000 (7.7% vs. 0%, P = 0.022) all contributed to decreasing ST-elevation myocardial infarction hospitalization revenue. One-year post-discharge financial follow-up revealed similar results: Insurance payments: $49,959 ± $53,741 vs. $35,937 ± $23,125, P = 0.044; Total hospital costs: $39,974 ± $37,434 vs. $26,778 ± $15,561, P = 0.007; Net Income: $9984 vs. $9159, P = 0.855. Conclusion All of the financial benefits of reducing door-to-balloon time in ST-elevation myocardial infarction go to payers both during initial hospitalization and after one-year follow-up. Trial Registration ClinicalTrials.gov ID: NCT00800163